2021
DOI: 10.1111/1346-8138.15929
|View full text |Cite
|
Sign up to set email alerts
|

Role of necroptosis in infection‐related, immune‐mediated, and autoimmune skin diseases

Abstract: As the body's largest organ, the skin mainly acts as a physical barrier.It is the first line of defense against infection and injury, protecting the body from potential attacks by exotic organisms or toxic substances.At the same time, it is essential for the regulation of temperature and humidity, substance metabolism, and so forth. The skin is also an interface with the external environment, and its sensory ability helps individuals to interact amicably with the environment. Because it is directly exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 77 publications
(66 reference statements)
0
21
0
Order By: Relevance
“…RNA sequencing (RNA-seq) data and clinical features were obtained from the TCGA database ( https://portal.gdc.cancer.gov/repository ) ( Liu et al, 2018 ) on 22 September 2021, including 473 tumor datasets and 41 normal datasets. Data for 31 necroptosis-related genes were obtained from the GSEA website ( https://www.gsea-msigdb.org/gsea ) and prior reviews ( Hanson, 2016 ; Chen et al, 2019 ; Molnár et al, 2019 ; Zhu et al, 2019 ; Liu et al, 2021b ). Before comparison, the expression data were standardized to fragment per kilobase million (FPKM) values ( Conesa et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…RNA sequencing (RNA-seq) data and clinical features were obtained from the TCGA database ( https://portal.gdc.cancer.gov/repository ) ( Liu et al, 2018 ) on 22 September 2021, including 473 tumor datasets and 41 normal datasets. Data for 31 necroptosis-related genes were obtained from the GSEA website ( https://www.gsea-msigdb.org/gsea ) and prior reviews ( Hanson, 2016 ; Chen et al, 2019 ; Molnár et al, 2019 ; Zhu et al, 2019 ; Liu et al, 2021b ). Before comparison, the expression data were standardized to fragment per kilobase million (FPKM) values ( Conesa et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, all patient information was randomly allocated into the training and the testing sets via the “caret” package in R (version 4.1.0, https://www.r-project.org/ ). A total of 39 necroptosis-related genes was acquired by searching published studies ( Hanson, 2016 ; Chen et al, 2019 ; Molnár et al, 2019 ; Zhu et al, 2019 ; Liu et al, 2021 ). In addition, the mutation data of STAD samples were downloaded in MAF format from the TCGA database.…”
Section: Methodsmentioning
confidence: 99%
“…org/). A total of 39 necroptosis-related genes was acquired by searching published studies (Hanson, 2016;Chen et al, 2019;Molnár et al, 2019;Zhu et al, 2019;Liu et al, 2021). In addition, the mutation data of STAD samples were downloaded in MAF format from the TCGA database.…”
Section: Data Collectionmentioning
confidence: 99%
“…Reddy et al [52] reported a pathway of regulated cell necrosis (necroptosis) in burn injury that involved death-receptor-mediated activation of RIPK3 (receptor-interacting serine/threonine-protein kinase 3). RIP kinases (RIPK1/RIPK3, necrosome) are critically involved in this caspase-independent pathway of regulated necrosis, which can be induced through a death receptor-dependent upstream pathway, leading to cell lysis and the release of immunogens [53,54]. In contrast to other diseases, such as cerebrovascular disease [55] and ischemia/reperfusion injury in skin flaps [56], blocking this pathway did not reduce cell death in thermally injured skin, which calls into question the importance of necroptosis in burns.…”
Section: Apoptosis Of the Skinmentioning
confidence: 99%